The Family After the Prenatal Death of a Child. Theological and Moral Aspects - Jan Dziedzic (Polonia Sacra)
The article is aimed at introducing the reader to the issue of the death of a child in the prenatal period and explaining difficult theological and moral aspects. The following issues are discussed: (1) The death of a child in the prenatal period, (2) The moral delimmas of the mother after her baby’s death (3) The duty to respect the body of a deceased child, (4) The moral duty to support the bereaved family. Miscarriage is most often due to a chromosomal abnormality (approximately 60–80% of cases) or other embryo/ foetal problems and is rarely based on choices made by women. After the death of the child, one must remember to respect the corpse. The basic moral obligation towards the deceased body is its dignified burial. The funeral of a stillborn child is not only an expression of the respect for the deceased child, but also is important for the family. It is very often the key to going through the mourning, and the basis of Christian comfort. The presented article will help the reader better understand the problems of the family after the loss of a child, provide answers to the moral dilemmas arising in this context and to teach the right attitudes towards people experiencing mourning after the loss of a loved one.